Improving Arabic Literacy with ChatGPT and Gamification: A Case Study at Alif Laam Miim Islamic School - Ahmad Shofiyyul Mubarok Asikin; Umi Hanifah; Abdullah Baihaqi; Riza Rifia; Qurrota A'yun (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
In the digital era, Arabic language education faces challenges in remaining relevant and engaging for digital-native learners. One promising solution is the integration of technologies such as ChatGPT and gamification into the learning process. This study investigates the effectiveness of these tools in improving Qira'ah (reading) and Kitabah (writing) skills among eighth-grade students at Islamic Secondary School Alif Laam Miim Surabaya. A mixed-methods approach was employed, combining quantitative and qualitative techniques. The study involved 30 students selected from a population of 60. Data collection methods included classroom observation, teacher and student interviews, and performance-based tests in reading and writing. Students completed tasks involving writing and reading simple sentences on the theme of “sports,” focusing on correct structure, pronunciation, and intonation. Data were analyzed using descriptive and inferential statistics, including paired sample t-tests. The results revealed a significant improvement in student performance, reading scores increased from 55.5 to 84.1 and writing from 53.5 to 83.4 (p < 0.001). ChatGPT contributed to improved grammatical accuracy and vocabulary development, while gamified platforms like Quizizz and Kahoot! enhanced student motivation and engagement. This study concludes that the integration of ChatGPT and gamification offers a practical, modern approach to Arabic instruction. It aligns with learners’ digital tendencies and encourages active, autonomous language use, suggesting a valuable model for 21st-century school education.